menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
If g(t) = 4 - 3t, then g(-2)=
asked
Nov 7, 2019
149k
views
5
votes
If g(t) = 4 - 3t, then g(-2)=
Mathematics
middle-school
XCRKx TyPHooN
asked
by
XCRKx TyPHooN
5.1k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
4
votes
plug -2 into the equation where t is, so 4 - 3( - 2 ). Multiply 3 and -2 first which is -6. 4 - (-6) is 4+6=10
Strix
answered
Nov 12, 2019
by
Strix
5.3k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.8m
questions
7.6m
answers
Other Questions
Solve for y in terms of x. 2/3y - 4 = x y = x + 6 y = -x + 4 y = -x + 6 y = x + 4
Aliyah has $24 to spend on seven pencils. After buying them she had $10. How much did each pencil cost?
Evaluate a + b when a = –16.2 and b = –11.4 A. –27.6 B. –4.8 C. 4.8 D. 27.6
What is the value of x? (-4) - x = 5
Find the quotient of 3,078 ÷ 27. A) 104 B) 109 C) 114 D) 119
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org